Effects of psychological, sensory, and metabolic energy prime manipulation on the acute endocrine stress response in fasted women. (December 2021) - Meier, Maria; Bentele, Ulrike U.; Benz, Annika B.E.; Denk, Bernadette; Dimitroff, Stephanie; Pruessner, Jens C.; Unternaehrer, Eva
Abstract: The stress response supports survival through energy mobilization. Paradoxically, a low blood glucose level dampens the endocrine stress response, and sugar consumption prior to stress restores it. Thus, energy availability may play a causal role in the endocrine stress response. Yet, it has never been tested whether sweet taste or expectations towards a drink content modulate the stress response. We investigated the potential role of sweetness, energy load and expectations towards energy load of a drink consumed prior to stress in restoring stress reactivity after fasting. N  = 152 women ( mean age =21.53, sd age =2.61) participated in the Trier Social Stress Test for groups in the morning after an overnight fast. Prior to stress induction, participants consumed a drink containing saccharose ( sugar, n  = 51), an equally sweet drink containing non-caloric sweetener ( sweetener, n  = 46), or water ( n  = 56). Additionally, participants in the sugar and sweetener group ( n  = 97) were informed whether or not their drink contained any calories ( energy prime ), which was deceptive in 50% of the cases. Eight salivary cortisol (−30, −20, −10, 0, +12, +25, +35, +45 min) and three blood glucose samples (−30, 0, +25 min) were assessed throughout the experiment. The effects of the experimental manipulations on cortisol trajectories were tested using multilevel mixed models. We found that compared with water, sugar and sweetener both significantly increased cortisol stress reactivity and with comparable intensity. However, our sensitivity analysis revealed a significant effect of sugar on cortisol trajectories compared to water and to sweetener. Drink-induced changes in blood glucose concentration were not associated with increases in cortisol. The energy prime did not affect the stress response. Overall, we could replicate the boosting effect of sugar consumption in a female sample after 8 h of fasting. The specific contribution of sweet taste and metabolic hormones to this boosting effect should be tested more rigorously in sex-balanced designs in the future. Highlights: Fasted women consumed sugar, non-caloric sweetener or water and underwent the TSST-G. Sugar consumption increased the cortisol stress response compared to water. The effects of sweetener consumption on the cortisol stress response are less conclusive in this study. Blood glucose changes after drink consumption were not related to the cortisol stress response.